PENGARUH KECERDASAN EMOSIONAL, MOTIVASI DAN KOMITMEN TERHADAP KINERJA GURU DI SMA PERSIAPAN STABAT KABUPATEN LANGKAT - Khairil Efendi (Jurnal Prodi Fakultas Ekonomi-UISU, 2020)
The formulation of the problem in this study is How is the influence of Emotional Intelligence, Motivation and Commitment to Teacher Performance in SMA Persiapan for Stabat Langkat Regency, both partially and simultaneously. The population and sample of this study were all teachers at the foundation, amounting to 37 people. The sampling technique uses total sampling. Data collection techniques used were direct interviews and questionnaires. The results of this study are partially the Emotional Intelligence variable has a positive and significant effect on Teacher Performance with tcount ttable, (2,432 2.04,), Motivation variable has a positive and significant effect on Teacher Performance with tcount ttable, (3,712 2 , 04) and Commitment Variables have a positive and significant effect on Teacher Performance with tcount ttable, (3.830 2.04). Simultaneously the variables of Emotional Intelligence, Motivation and Commitment have a positive and significant effect on Teacher Performance with Fcount Ftable, (12,201 2.87). R2 (RSquare) value of 0.540, which means that the variable Emotional Intelligence, Motivation and Commitment has a positive and significant effect on Teacher Performance in SMA Persiapan for Stabat Langkat Regency by 55.60%, and the remaining 44.40% again, influenced by factors other factors not examined.